REPRESENTASI FAMILY CAREGIVING DALAM FILM HOW TO MAKE MILLIONS BEFORE GRANDMA DIES (2024) - Aulia Retno Utami; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study aims to examine the portrayal of family caregiving in How to Make Millions Before Grandma Dies (2024) movie and to unveil the myths within the media text. Theoretically, this research applies Stuart Hall’s Theory of Representation, supported by the Ethic of Care framework, and utilizing Roland Barthes’ Semiotic analysis as its methodological approach. The primary findings indicate that How to Make Millions Before Grandma Dies (2024) movie represents family caregiving as a relational practice grounded in interpersonal relationships and emotional proximity between caregiver and care-receiver. Furthermore, this study reveals the naturalization of family caregiving as an inherently female domain, exemplified through the character of M, who must navigate personal negotiations to engage in intensive caregiving practice. Based on these findings, it can be concluded that How to Make Millions Before Grandma Dies (2024) portrays family caregiving as a relational and affective practice, while simultaneously reinforcing the notion of family caregiving as a natural domain of femininity.